Perfect Competition in an Oligoply (including Bilateral Monopoly) - Pradeep Dubey; Dieter Sondermann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
We show that if limit orders are required to vary smoothly, then strategic (Nash) equilibria of the double auction mechanism yield competitive (Walras) allocations. It is not necessary to have competitors on any side of any market: smooth trading is a substitute for price wars. In particular, Nash equilibria are Walrasian even in a bilateral monopoly.
Keywords: C72; D41; D44; D61; 330; Limit orders; double auction; Nash equilibria; Walras equilibria; mechanism design; Auktionstheorie; Nash-Gleichgewicht; Allgemeines Gleichgewicht; Mechanism Design; Oligopol; Bilaterales Monopol; Theorie